CoNi alloy nanoparticles coated with carbon layer doped with P atom for efficient hydrogen evolution reaction. (26th October 2021) - Yu, Chunjie; Zhai, Xingwu; Wu, Pengcheng; Zhu, Zhaoqing; Peng, Banghua; Ge, Guixian; Liu, Zhiyong
Abstract: Low cost, high activity and stability electrocatalysts for hydrogen evolution reaction (HER) have been extensively studied in recent years. We have successfully synthesized a transition metal phosphide electrocatalyst (CoNi@CP) with coating structure. The CoNi@CP was prepared with the mild conditions. An organophosphorus ligand was synthesized by simple organic reaction. It was synthesized by coordination with Co 2+ and Ni 2+ and then calcined. CoNi@CP has abundant and uniform phosphorus atom doping, no energy consumption in phosphating process, and avoids the generation of highly toxic gas PH3 . Because of its special coating structure, the adsorption of H ∗ on its surface was enhanced, and the active center of CoNi was protected, which contributed greatly to the improvement of catalytic performance. At 10 mA/cm 2 current density, the overpotential of the catalyst only 74 mV, and the slope of Tafel was only 83 mVdec -1 . The performance of the catalyst remained unchanged after 1000 stability tests. In addition, we had proved theoretically that the catalyst had high HER activity by DFT calculation. Therefore, it provides inspiration for us to better develop efficient transition metal phosphide electrocatalysts. Graphical abstract: Carbon coated electrocatalyst CoNi@CP was synthesized by simple organic reaction synthesis and organophosphorus ligand, and then calcined by coordination with Co and Ni. The overpotential of HER in alkaline medium is only 74 mV and has good stability. Image 1 Highlights: Uniform phosphorus doping and no toxic PH3 were achieved. CoNi@CP showed a significant HER activity. DFT was used to verify that CoNi@CP with carbon coating structure has good activity and stability.